A review and analysis of existing legal and policy issues related to land tenure and agriculture in Nepal - Sharma, K; Khanal, SN (Kathmandu University Journal of Science, Engineering and Technology, 2010)
This review takes stock of current legislative provisions and policies pursued by the Government of Nepal with regard to agriculture and land tenure. Currently, land tenure issues are primarily governed under the legislations enacted by the Ministry of Land Reform and Management, while there are a number of policies formulated in order to facilitate agricultural production by the Ministry of Agriculture and Cooperatives, Ministry of Water Resources for irrigation regulation, Ministry of Forest and Soil Conservation through Leaseholds forestry programme. The Government of Nepal has already amended the Land Act, 2021 B.S. twice. Each amendment has targeted something other than ceilings. Amendments in regulation and devising other sectoral policies have not adequately discussed nor have encouraged sustainable land management. New and innovative policies are required to prevent degradation and achieve sustainable management of the precious land resource base of the country. DOI: 10.3126/kuset.v6i2.4022 Kathmandu University Journal of Science, Engineering and Technology Vol.6. No II, November, 2010, pp.133-141